Marketing Strategies for Electronic Companies in Punjab - Malhotra, Parinita; Singh, Harpreet (Gyan Management Journal, 2019)
The word "Strategy "comes from Greek word, Strategies which means a "general”. At that time, strategy, literally meant, the art and science of directing military Focus. The term strategy is used in business to describe how an organisation is going to achieve its objective and mission. Most of the business organisations have several options for accomplishing their goal marketing strategy is also one of them. Strategy also include the determination and evaluation of alternative paths to achieve the objectives. Focus of the present work is to discover or examine how marketing strategies enable producing business firms dealing in Electronic goods in Punjab can achieve their targets or objectives and what are the needs ,wants, interest, perceptions and behaviours of customers threats. It further interest to know how customer purchase, Televisions, Refrigerators, Room air conditioners, ceiling and Table fans, washing machines, geasures, Electronic goods used in kitchens etc. These electronic goods reflect the economic and behaviour pattern of the consumers. Researcheris of the view that these electronic goods are very much relevant to the consumers of Punjab and they show keen interest to buy them. Prime objective of the study is to measure the impact of marketing strategies on the buying pattern/behaviour of consumers of Punjab of these electronic goods. Marketing begins much before the production of goods and services and continues even after the sale.